Association between Severity of Tooth Wear and Dentinal Hypersensitivity - Ayer, Ashok (Journal of College of Medical Sciences-Nepal, 2016)
Background & Objectives: Tooth wear (attrition, abrasion, erosion, and abfraction) is perceived globally as ever increasing problem. Several outcome of the tooth wear are hypersensitivity, esthetic problems, functional impairment, annoyance to the patient, and fracture of the tooth. Among these, the measurable and more commonly reported outcome is hypersensitivity to stimuli. Although dentin hypersensitivity is a common clinical condition and is generally reported by the patient after experiencing a sharp, short pain caused by one of the several different external stimuli, it is often inadequately understood. None of the scientific literature available till date attempted to establish the relationship between tooth wear and dentin hypersensitivity which could be a key factor in monitoring those patients. The aim of the study was to estimate the association between severity of teeth wear and sensitivity in the patients with reported dentinal hypersensitivity. Materials & Methods: Fifty patients with dentin hypersensitivity were investigated for tooth wear. Tooth wear measured using exact tooth wear index and level of sensitivity to stimuli was recorded using a numerical rating scale. Results: Enamel wear at cervical region of teeth showed a positive correlation (p=.010), similarly, dentin wear at cervical region of teeth showed positive correlation and significant association (p<.001) with dentinal hypersensitivity. Conclusion: The observation supports a significant association between severities of tooth surface wear and dentinal hypersensitivity.